The influence of leadership, workload, and work dicipline on employee performance at XYZ Broadcast Institution - Wahidah, Siti Ulfa Nur; Siddiq, Andhika Mochammad; Ismail, Gurawan Dayona; Saputro, Arie Hendra (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to examine the impact of leadership, workload, and work discipline on employee performance at XYZ Broadcasting Institution. The samples in this study were employees, with a total sample size of 120. This study employs quantitative methodologies, including probability sampling procedures (saturated samples) and data processing tools based on the SPSS version 25.0 program. According to the findings of research conducted at the XYZ Broadcasting Institute, Leadership has a significant positive effect on employee performance, Workload has a significant positive effect on employee performance, and Work Discipline has a significant positive effect on employee performance. The findings of this study highlight the significance of these variables in managing employee performance.